Perancangan User Interface Aplikasi Konsultasi Disabilitas dengan Metode Design Thinking untuk Mendukung Aksesibilitas dan Partisipasi Sosial Masyarakat - Febrina Larasati (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2024)
In Indonesia, the paradigm towards people with disabilities is still considered a negative stigma for the majority of society and social discrimination unconsciously arises in society. To overcome this problem, it is necessary to empower people with disabilities so that they are no longer a group of social discrimination in society. The lack of information about disability, disability therapy, appropriate therapists, and the credibility check of therapists are also obstacles faced by people with disabilities and their relatives. Therefore, in an effort to support disability empowerment measures, a user interface (User Interface/User Experience) was designed for a disability consultation application called